A footstep and piezoelectric sensor-based power generation system - Yonis M Yonis, Buswig; Norhuzaimin, Julai; Al-Khalid, Hj Othman (2022)
In this paper, the energy harvesting capacity of piezoelectric material is applied a footstep energy generation system. Conventional fossil fuels have raised concern about sustenance of the environment. As a means of reducing dependence on fossils fuels, the piezoelectric sensor is touted as a viable replacement. Piezoelectric materials are used to generate alternating current (AC) and direct current (DC) for powering communication devices, lightings and battery charging. 500 modified piezoelectric tiles were assembled to generate required power was then routed to an electronic processing unit containing a microcontroller, voltage rectifier and regulator circuitry. The output can deliver power to a phone, light bulb and battery. Using footsteps, the designed system delivered a maximum power of 4.25 W with full load current of 2.08 A. The 12V 10 Ah battery charging time is 31.25 hours and the full load battery life is 4.81 hours. The designed system was verified via simulation and experimentally. This system can be useful during when grid electricity is disrupted.